Panorama historique sur les plantes alimentaires à féculents en Afrique centrale - Serge Bahuchet (Revue d'ethnoécologie)
In Central African rainforests, tubers (yams, cassava, Araceae) are staple food, together with plantains. This series of starchy food species results from histories, some very old, others more recent, after complex routes involving several continents. Here we draw a panorama of introduction, use and distribution into the local societies of starchy food, either wild or cultivated. Finally we show how these plants were integrated into the agricultural and food systems, and which utensils are used for their processing.